Tren Baru Program Deradikalisasi Di Lingkungan Organisasi Pemuda Muslim Indonesia - Novia Elok Rahma Hayati; Nur Ali; Nabila Nur Bakkah Nazrina (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
The deradicalization program is one of the solutions as a new trend to tackle the problem of radicalism in Indonesian youth, especially among Muslim youth organizations. Therefore, this deradicalization program is intensively carried out as a form of counter-terrorism action. This paper aims to explain the deradicalization trend carried out by Muslim youth organizations, namely the Nahdlatul Ulama Student Association (IPNU) and the Muhammadiyah Student Association (IPM) in Malang City. Interviews, observations, and data analysis carried out resulted in the findings that the Deradicalization program was contained in several forms of activities. In the IPNU environment, there are 3 activities, namely formal cadre activities in the form of Makesta and Lakmud, then non-formal cadre activities, namely in the form of discussions and literacy, then routine classic book studies and eventual activities in the form of tahlil, sholawat dhiba 'and khatmil Quran. While in the IPM environment there are literacy discussions which are held regularly once a week, Darul Arqam activities are held in the month of Ramadan, and incidental activities in the form of recitations which are held 2 times a week.